Use, Perceived Usability, and Barriers to Implementation of a Patient Safety Dashboard Integrated within a Vendor EHR - Bersani, Kerrin; Fuller, Theresa E.; Garabedian, Pamela; Espares, Jenzel; Mlaver, Eli; Businger, Alexandra; Chang, Frank; Boxer, Robert B.; Schnock, Kumiko O.; Rozenblum, Ronen; Dykes, Patricia C.; Dalal, Anuj K.; Benneyan, James C.; Lehmann, Lisa S.; Gershanik, Esteban F.; Bates, David W.; Schnipper, Jeffrey L. (Applied Clinical Informatics, 2020)
Background Preventable adverse events continue to be a threat to hospitalized patients. Clinical decision support in the form of dashboards may improve compliance with evidence-based safety practices. However, limited research describes providers' experiences with dashboards integrated into vendor electronic health record (EHR) systems.Objective This study was aimed to describe providers' use and perceived usability of the Patient Safety Dashboard and discuss barriers and facilitators to implementation.Methods The Patient Safety Dashboard was implemented in a cluster-randomized stepped wedge trial on 12 units in neurology, oncology, and general medicine services over an 18-month period. Use of the Dashboard was tracked during the implementation period and analyzed in-depth for two 1-week periods to gather a detailed representation of use. Providers' perceptions of tool usability were measured using the Health Information Technology Usability Evaluation Scale (rated 1–5). Research assistants conducted field observations throughout the duration of the study to describe use and provide insight into tool adoption.Results The Dashboard was used 70% of days the tool was available, with use varying by role, service, and time of day. On general medicine units, nurses logged in throughout the day, with many logins occurring during morning rounds, when not rounding with the care team. Prescribers logged in typically before and after morning rounds. On neurology units, physician assistants accounted for most logins, accessing the Dashboard during daily brief interdisciplinary rounding sessions. Use on oncology units was rare. Satisfaction with the tool was highest for perceived ease of use, with attendings giving the highest rating (4.23). The overall lowest rating was for quality of work life, with nurses rating the tool lowest (2.88).Conclusion This mixed methods analysis provides insight into the use and usability of a dashboard tool integrated within a vendor EHR and can guide future improvements and more successful implementation of these types of tools.
Keywords: clinical decision support; health information technology; electronic health record; patient safety; information/data visualization; usability; dashboard